Optimizacion De Perforacion Y Voladura Aplicando El Modelo Matematico De Roger Holmberg En Frentes De 3.5m*3m En Roca Tipo Ii Veta Papagayo. Mina Poderosa. 2017 - Quezada Jacobo, Wilmer Ubemar (2017)
The unitary drilling and blasting operations are very versatile and require constant attention to obtain good results. These unit operations on the fronts of powerful mining company are at high cost due to a lack of proper design of drilling and blasting meshes, the performance or advancement per shot are low, the indicators of these operations are not optimal and are record large number of failed shots monthly; for which it was proposed to design new drilling meshes using the mathematical model of Roger Holmberg. The application of the mathematical model of Roger Holmberg to properly design the drilling mesh and distribute the quantity of explosive correctly in each drill has allowed to reduce the amount of explosive per firing, reduction of consumption of drilling steels, reduction of blown firings, rounded shots and shots cut, reduction of the number of holes to be drilled; all of which reduced the cost of these unit operations per linear meter from US $ 715.55 / m to US $ 586.31 / m in addition to increasing the advance per shot from 1.43 m to 1.7 m.